Hippo Signaling in the Heart – Non-Canonical Pathways Impact Growth, Survival and Function - Re, Dominic P. Del (Circulation Journal, 2016)
Initially identified inDrosophila melanogaster, the Hippo signaling pathway regulates organ size through modulation of cell proliferation, survival and differentiation. This pathway is evolutionarily conserved and canonical signaling involves a kinase cascade that phosphorylates and inhibits the downstream effector Yes-associated protein (YAP). Recent research has demonstrated a fundamental role of Hippo signaling in cardiac development, homeostasis, injury and regeneration, and remains the subject of intense investigation. However, 2 prominent members of this pathway, RASSF1A and Mst1, have been shown to influence heart function and stress responses through YAP-independent mechanisms. This review summarizes non-canonical targets of RASSF1A and Mst1 and discusses their role in the context of cardiac hypertrophy, autophagy, apoptosis and function. (Circ J 2016; 80: 1504–1510)